Suburbanization and residential desegregation in South Africa's cities - Wim Naudé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Population density gradients for South Africa's cities are quite small in absolute value, indicating a relatively flat population distribution across the cities. In contrast employment is less flatly distributed than the population. The relationship between employment densities and distance across South African cities has remained constant between 1996 and 2001 whilst there has been on average a slight increase in population density further away from the city centres. As per capita income of the population rises, density in the central city areas decreases. Employment growth has no significant impact on suburbanization indicating that population settlement does not necessarily follow jobs. Finally, it is found that there have been decreases in segregation in South Africa's metropolitan cities since 1996 especially in the former white group areas, which could suggest that the formerly spatially excluded black population is slowly moving into former white areas, which are also closer to where economic activities are located.
Keywords: R23; R11; O55; 330; suburbanization; segregation; South Africa